A discrete event simulation model of compressive creep for LDPE - Seyyed Saeed Vaezzadeh; Md Mahbubur Rahman; Alireza Godsi Chafjiri; Robert Kelley Bradley (Results in Engineering)
Experimental results from compressive creep measurements of LDPE samples using a custom-built rig exhibited scatter in the secondary (phase II) creep region that deviated from the expected smooth curve. Inspection of the data revealed a pattern to the scatter consistent with straight-line linear segments that randomly switched between three distinct creep rates (i.e. slopes). Further experiments and analysis provide evidence that the segmentation is not directly dependent on temperature but changes in temperature influence the probability of segment breakpoint occurrence. Our literature survey did not identify any existing creep models to describe this behavior, so we present a probabilistic model here. The model treats changes between the three creep rates as a discrete event with probability of occurrence dependent on temperature as well as a number of parameters to be estimated from experimental data and/or determined via best-fit optimization. The model is an accelerated method of estimating creep, and it provides a means for estimating both the average secondary creep and the expected scatter for a given temperature profile.